Analysis of the Effect of Leadership Style towards Employee Performance with Job Satisfaction as Mediator and Gender as Moderator - Ardiansyah Irwan Saputra (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Employee performance is an important component in influencing the effectiveness and success of the company. Therefore, factors for enhancing employee performance need to be determined. The research aims to analyze the effect of leadership style on employee performance with job satisfaction as a mediator and gender as a moderator. It is included in descriptive quantitative research, in which is conducted at PT. Toyo Kanestu Indonesia, involving 300 employees as the research sample. The data analysis technique in this study used Partial Least Square (PLS). The results obtained in this research is that there is a significant and positive effect between job satisfaction, gender, and leadership style on employee performance, leadership style on employee performance mediated by job satisfaction, and no effect between leadership style and job satisfaction on employee performance moderated by gender. The suggestion from the result of this research is company leaders are expected to apply a good leadership style in order to achieve good performance from their employees. Other than that, it is hoped that further research will add variables that have not been studied in this study.